The COVID-19 Student WorkForce at the Icahn School of Medicine at Mount Sinai: A Model for Rapid Response in Emergency Preparedness. (25th May 2021) - Bahethi, Rohini R.; Liu, Benjamin Y.; Asriel, Benjamin; Blum, James R.; Huxley-Reicher, Zina; Agathis, Alexandra Z.; Pathak, Shravani; Sainte Willis, Michelle; Muller, David
Abstract : Supplemental Digital Content is available in the text. Abstract : Problem: In accordance with guidelines from the Association of American Medical Colleges, medical schools across the United States suspended clerkships and transitioned preclinical courses online in March 2020 because of the COVID-19 pandemic. Hospitals and health systems faced significant burdens during this time, particularly in New York City. Approach: Third- and fourth-year medical students at the Icahn School of Medicine at Mount Sinai formed the COVID-19 Student WorkForce to connect students to essential roles in the Mount Sinai Hospital System and support physicians, staff members, researchers, and hospital operations. With the administration's support, the WorkForce grew to include over 530 medical and graduate students. A methodology was developed for clinical students to receive elective credit for these volunteer activities. Outcomes: From March 15, 2020, to June 14, 2020, student volunteers recorded 29, 602 hours (2, 277 hours per week) in 7 different task forces, which operated at 7 different hospitals throughout the health system. Volunteers included students from all years of medical school as well as PhD, master's, and nursing students. The autonomous structure of the COVID-19 Student WorkForce was unique and contributed to its ability to quickly mobilize students to necessary tasks. The group leaders collaborated with other medical schools in the New York City area, sharing best practices and resources and consulting on a variety of topics. Next Steps: Going forward, the COVID-19 Student WorkForce will continue to collaborate with student leaders of other institutions and prevent volunteer burnout; transition select initiatives into structured, precepted student roles for clinical education; and maintain a state of readiness in the event of a second surge of COVID-19 infections in the New York City area.